Implementation of the GDLC Method in Developing RPG Educational Games to Improve Student Learning Outcomes in the Introduction of the 25 Prophets - Makmun ZA; Ronal Yulyanto Suladi; Neng Linda Badratul Laela; Fiqih Hana Saputri; Rudi Setiyanto (Universitas Islam Raden Rahmat, Malang, 2026)
Learning media innovation is rapidly evolving alongside digital technology, particularly through the use of educational games. This study aims to develop and evaluate an interactive RPG-based educational game to introduce the 25 Prophets to primary school students. The research employs the Game Development Life Cycle (GDLC) method, which systematically covers six phases: initiation, pre-production, production, testing, beta, and release. During these stages, the game was designed to integrate short stories, educational resources, and comprehension tests into an immersive RPG environment. The application was tested with students at SDN 3 Jati to measure its effectiveness. The results indicate a significant improvement in student learning outcomes; the average pre-test score of 55% rose to 85% in the post-test, reflecting a 30% increase in comprehension. Furthermore, user satisfaction surveys rated the application's usability and interface design as